Takhassus Center Program in Reading Yellow Book (Kitab Kuning) for Grade VIII Students of MTsN 3 Jombang - Satiti, Wisnu Siwi; Hidayatulloh, Muh Syarif; Khotimah, Khusnul (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Education has a central role in shaping qualified individuals who are ready to face global challenges. Islamic education, especially through madrasah, has a special responsibility in developing the religious aspects of students. In connection with the management of educational programs, MTsN 3 Jombang has 3 excellent programs, one of which is the Takhassus Center. The program has 3 branches of boarding school material which include the fields of Tahsin / Tahifdhul Quran, Worship Practices and Reading the Book, and this research only focuses on the field of reading yellow book (kitab kuning). This study aims to analyze more deeply as well as describe the planning management of the takhassus center program in the field of reading the book, the management of the implementation of the takhassus center program in the field of reading the book and the evaluation management of the takhassus center program in the field of reading yellow book (buku kuning). This study employs qualitative approach method with a type of case study. In collecting data, researchers employ triangulation data analysis techniques which include observation, open interviews and documentation, research conducted at MTsN 3 Jombang. The results showed that the management of the takhassus center program in the field of reading kitab class VIII MTsN 3 Jombang was carried out by the process of Planning, Implementation, Program evaluation both from the aspect of written and oral exam assessment to measure students' understanding of the contents of the yellow book.